Electroencephalographic and Epilepsy Findings in ZNF711 Variants: A Case Series of Two Siblings - Michele Minerva; Lorenzo Perilli; Samanta Carbone; Margherita Maria Rossi; Federica Lotti; Luisa Lonoce; Maria Rosaria Curcio; Salvatore Grosso (Neurology International)
Background/Objectives: ZNF711(Zinc finger protein 711) encodes a zinc finger protein of currently undefined function, located on the X chromosome. Current knowledge includes a limited number of case reports where this gene has been exclusively associated with X-linked intellectual disability (XLID). As far as we are aware, we report the first cases of epilepsy associated with this particular variant. Our aim is to further delineate the phenotypic spectrum of ZNF711 gene pathogenic variants, adding clinical features to this rare condition, following a genotype-first approach. Case presentation: We describe the familiar case of two male siblings presenting with moderate intellectual disability (ID), language delay, and motor stereotypies. Additionally, they experienced generalized tonic–clonic seizures (GTCSs) and myoclonic seizures with interictal electroencephalographic abnormalities. Both children underwent various genetic testing and counselling, including an extended next-generation sequencing (NGS) panel, revealing a hemizygous c.657C > G pathogenic variant in the ZNF711 gene from maternal inheritance. Conclusions: This case expands the clinical range of ZNF711 variants by highlighting epilepsy as a potential comorbidity and suggesting other possible causal candidates for generalized epilepsy. Moreover, it emphasizes the need for further research into the phenotypic spectrum associated with this variant.